FREQUENCY OF HEPATITIS B AND C IN PATIENTS SEEKING TREATMENT AT THE DENTAL SECTION OF A TERTIARY CARE HOSPITAL - Fayyaz, Muhammad; Ghous, Shah Mohammad; Ullah, Fahim; Abbas, Irum; Ahmed, Nofil; Ahmed, Ans (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hepatitis B and C are serious health problems and a major cause of liver disease worldwide. Like medical patients, dental patients are at increased risk of getting hepatitis B and C viral infection during various procedures. Keeping in view the rising incidence of hepatitis B and C in Pakistan, it was considered important to know about the frequency and distribution of HBV and HCV in patients undergoing various procedures during treatment in dentistry section. Methods: This study was based on the review of the records of the patients visiting the dental section of Ayub Teaching Hospital Abbottabad between April to December 2014. The Secondary data of 3549 patients who visited the dental section for treatment during this period was used for this study. Results: Male patients constituted 53.9% (1914) and female patients were 46.1% (1635) of total screened patients. Total infection with hepatitis B and C were found in 4.1 % (147) of the screened patients. Out of these infections, hepatitis C was found in 66% (97) patients and hepatitis B in 32.7% (48), whereas 1.3% (2) of the patients had both the infections. Infection with hepatitis B and C viruses was detected in 39.5% (58) male patients and 60.5% (89) female patients. Alarmingly high proportions of new 75.5% (111) cases of both the infections were detected during the nine month period. Conclusion: Due to high prevalence of HBV and HCV among patients coming for dental treatment, it is recommended that regular screening for HBV and HCV be performed on every patient before carrying out any procedure upon. Keywords: Hepatitis B, Hepatitis C, dental care, screening